2011
DOI: 10.4314/ijbcs.v5i2.72087
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of organic compost and NPK fertilizer on soil fertility, yield and quality of amaranth in southwest Nigeria

Abstract: The need for an increased production of vegetables to meet the dietary vitamin requirements of the people had necessitated a research in the use of manure in improving the soil fertility for an improved yield and quality of amaranth. The research was conducted in Obasoto Farm (latitude 7°10'N and longitude 5°37'E) in Owo Local Government Area of Ondo State, Nigeria in the early and late seasons of 2007, 2008 and 2009. The experimental design was a randomized complete block with three treatments replicated thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
4
3
1
Order By: Relevance
“…Beta-Carotene was observed to be highest in plants derived from 10 t ha -1 sewage sludge treatments for both varieties and was significantly different from the other treatments. The results of this study are in agreement with Arisha et al [36] on pepper cultivars, Abdelrazzag [17] on onion and Mofunanya et al [35] on Amaranthus spinosus L. Niacin was highest for plants treated with 70 k ha -1 NPK compound fertilizer for both varieties and was significantly different among the treatments. This may be attributed to high amounts of nitrogen in NPK fertilizer compared to the organic fertilizers.…”
Section: Micronutrient Composition Of Amaranthus Caudatus (Samaru Locsupporting
confidence: 92%
See 1 more Smart Citation
“…Beta-Carotene was observed to be highest in plants derived from 10 t ha -1 sewage sludge treatments for both varieties and was significantly different from the other treatments. The results of this study are in agreement with Arisha et al [36] on pepper cultivars, Abdelrazzag [17] on onion and Mofunanya et al [35] on Amaranthus spinosus L. Niacin was highest for plants treated with 70 k ha -1 NPK compound fertilizer for both varieties and was significantly different among the treatments. This may be attributed to high amounts of nitrogen in NPK fertilizer compared to the organic fertilizers.…”
Section: Micronutrient Composition Of Amaranthus Caudatus (Samaru Locsupporting
confidence: 92%
“…The 10 t ha -1 of poultry manure gave the highest level of vitamin C for Amaranthus caudatus (Samaru local variety) which was significantly (p<0.05) different among the treatments while plants submitted to 70 kg ha -1 of NPK was found to be highest for the Amaranthus cruentus (NH84/452) but there was no significant difference among the treatments. Similar findings were reported by Mofunanya et al [33] on Amaranthus spinosus L. and Adekayode and Ogunloya [35] on amaranth in southwest Nigeria. Virtually, vitamin C was high in plants treated with organic matter content which leads to an increase in soil microbial population, while high microbial population had been reported to improve the antioxidant capacity of the soil which could lead to availability of the substrates for vitamin C biosynthesis.…”
Section: Micronutrient Composition Of Amaranthus Caudatus (Samaru Locsupporting
confidence: 88%
“…External influences can be further classified into natural variables such as sunlight, soil moisture, soil pH, and soil respiration as well as artificial factors or elements that are purposely provided by humans (Barron-Gafford et al, 2011;Prasad et al, 2017), such as the biofertilizer provided to aid plant development in this study. Additionally, soil fertility can be increased, resulting in an increase in the productivity of plants, through the application of biofertilizers (Adekayode & Ogunkoya, 2011). However, the results of this study indicated that plants grown without biofertilizer had the highest average plant height and leaf number values when compared to other treated plants.…”
Section: Resultscontrasting
confidence: 62%
“…It has also been observed that some ammonia-N may be lost through volatization in the process of composting hence reducing the content of N that could be supplied from compost compared to FYM (Rosen & Bierman, 2014). Adekayode and Ogunkoya (2011) observed higher N content in plots treated with organic fertilizer attributing this observation to direct input of N and ability of manure to make N available for a long time due to slower release of N from the high residual pool.…”
Section: Influence Of Cropping Systems and Organic Fertilizers On Totmentioning
confidence: 88%